2022
DOI: 10.1007/s00426-022-01705-8
|View full text |Cite
|
Sign up to set email alerts
|

Perception and action as viewed from the Theory of Event Coding: a multi-lab replication and effect size estimation of common experimental designs

Abstract: The Theory of Event Coding (TEC) has influenced research on action and perception across the past two decades. It integrates several seminal empirical phenomena and it has continued to stimulate novel experimental approaches on the representational foundations of action control and perceptual experience. Yet, many of the most notable results surrounding TEC originate from an era of psychological research that relied on rather small sample sizes as judged by today’s standards. This state hampers future research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 183 publications
1
8
0
Order By: Relevance
“…Furthermore, a study that replicated numerous original studies has reported even smaller effect sizes in the order of d = 0.15 (Klein et al, 2018). These findings align with the work by Schäfer and Schwarz (2019), who also found that effects from replications of studies were considerably smaller as compared to the original studies (see Janczyk et al, 2022, as a an example). Thus, we urge researchers to make an educated decision regarding the expected effect size when performing power analyses.…”
Section: The Focus Of This Tutorialsupporting
confidence: 80%
“…Furthermore, a study that replicated numerous original studies has reported even smaller effect sizes in the order of d = 0.15 (Klein et al, 2018). These findings align with the work by Schäfer and Schwarz (2019), who also found that effects from replications of studies were considerably smaller as compared to the original studies (see Janczyk et al, 2022, as a an example). Thus, we urge researchers to make an educated decision regarding the expected effect size when performing power analyses.…”
Section: The Focus Of This Tutorialsupporting
confidence: 80%
“…Response times (RTs) were shorter in the compatible than in the incompatible condition, despite the action effect occurring only after RT was already measured. This REC effect has been replicated in numerous studies with spatial overlap between responses and effects (e.g., Janczyk et al, 2017Janczyk et al, , 2023Pfister & Kunde, 2013), but also with overlap of the intensity (e.g., Kunde, 2001, Exps 2-3) or duration of responses and effects (e.g., Kunde, 2003). Anticipated action effects have also been considered as a source of the commonly occurring performance costs in multitasking (Schacherer & Hazeltine, 2020Wirth et al, 2018; for a review, see .…”
Section: Ideomotor Theory and Response-effect Compatibilitymentioning
confidence: 78%
“…The results they observed were in line with the idea of ideomotor action: Participants were significantly more likely than chance (i.e., 60.1%) to respond with the action that had preceded the presented tone in the learning phase, than the with the other action. Even though this effect was only obtained with 12 participants, it has recently been replicated with larger samples (Janczyk et al, 2023;Sun et al, 2020) and this free-choice task is one of the dominant paradigms for investigating ideomotor effects in the literature (see Shin et al, 2010).…”
Section: Contemporary Evidence For Ideomotor Learningmentioning
confidence: 92%